Efektifitas E-Modul Berbasis Problem Solving Terhadap Keterampilan Berfikir Kritis Perserta Didik - Wahyuni, Dila; Sari, Milya; Hurriyah, Hurriyah (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
The purpose of this study is to look at the effectiveness of problem solving based e-modules on students' critical thinking skills. The pre-experimental research method used the one shot case study design. The instruments used are tests that are used to see students' critical thinking skills. The research sample was students of class X MIPA 4 SMA N 2 Lubuk Basung. The results showed the e-module was very effective at developing students' critical thinking skills. The acquisition of critical thinking ability scores on IDEALS aspects as follows: I (Identify) 83.33% the category is very effective; D (Define) 86.66% very effective category; E (Enumerate) 85.55% in the highly effective category; A (Analyze) 83.33% very effective category; L (List) 83.33% very effective category; and S (Selt-Correct) 81.81% in the highly effective category. This shows that e-module based on problem solving can be used to develop critical thinking skills of high school class X students on straight motion and parabolic motion material.